Malaria in Pregnancy Interacts with and Alters the Angiogenic Profiles of the Placenta. - Ricardo Ataíde; Oscar Murillo; Jamille G Dombrowski; Rodrigo M Souza; Flávia A Lima; Giselle F M C Lima; Angélica D Hristov; Suiane C N Valle; Silvia M Di Santi; Sabrina Epiphanio; Claudio R F Marinho (Public Library of Science (PLoS), 2015)
Malaria in pregnancy remains a substantial public health problem in malaria-endemic areas with detrimental outcomes for both the mother and the foetus. The placental changes that lead to some of these detrimental outcomes have been studied, but the mechanisms that lead to these changes are still not fully elucidated. There is some indication that imbalances in cytokine cascades, complement activation and angiogenic dysregulation might be involved in the placental changes observed. Nevertheless, the majority of studies on malaria in pregnancy (MiP) have come from areas where malaria transmission is high and usually restricted to Plasmodium falciparum, the most pathogenic of the malaria parasite species. We conducted a cross-sectional study in Cruzeiro do Sul, Acre state, Brazil, an area of low transmission and where both P. vivax and P. falciparum circulate. We collected peripheral and placental blood and placental biopsies, at delivery from 137 primigravid women and measured levels of the angiogenic factors angiopoietin (Ang)-1, Ang-2, their receptor Tie-2, and several cytokines and chemokines. We measured 4 placental parameters (placental weight, syncytial knots, placental barrier thickness and mononuclear cells) and associated these with the levels of angiogenic factors and cytokines. In this study, MiP was not associated with severe outcomes. An increased ratio of peripheral Tie-2:Ang-1 was associated with the occurrence of MiP. Both Ang-1 and Ang-2 had similar magnitudes but inverse associations with placental barrier thickness. Malaria in pregnancy is an effect modifier of the association between Ang-1 and placental barrier thickness.